Technique and Tectonic Concepts as Theoretical Tools in Object and Space Production: An Experimental Approach to Building Technologies I and II Courses - Murat Sönmez (Buildings)
By focusing on technical content, this study presents ‘two experimental building technologies courses’ connecting the conceptual and practical aspects of architectural object production. Built on the fundamental ‘concept of making’, these courses encourage students to explore their creative abilities by uniting material, form, and purpose. In the Building Technologies I course, exploration starts with the concept of ‘technique’, which involves the practical and theoretical knowledge necessary to shape architectural objects. This technique allows the production of architectural objects that encapsulate spaces carrying action and time, making a mere explanation of space creation insufficient. Thus, in the Building Technologies II course, the focus shifts to the ‘tectonic’ concept, which involves creating coherent spatial entities within a single structural system. The two courses aim to equip students with the ability to develop their unique knowledge and methods for construction before advancing to more theorised Building Technologies courses. Students are encouraged to engage with materials to uncover their potential, experiment with forms to achieve design goals, and personalise construction processes. This proposal advocates for foundational construction courses built on intuitive knowledge to replace traditional rational knowledge courses. Our study presents the methodologies and outputs of the proposed Building Technologies courses as a basis for ongoing construction courses.